2019
DOI: 10.3329/bjz.v47i2.44342
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of parasites in domestic ducks from rural areas of Narayanganj

Abstract: Thirty six domestic ducks (Anas platyrhynchos) were examined to observe the occurrence of ecto and endoparasites. Altogether seven species of ectoparasites namely Anaticola crassicornis, Lipeurus caponis, Goniocotes hologaster, Menopon gallinae, Menacanthus stramineus, Holomenopon leucpxanthum and Dermanyssus gallinae were observed and identified. L. caponis showed the highest prevalence both in male and female (100%). Mean intensity of A. crassicornis in female ducks was the highest (14.5 ± 2.36) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Drepanidotaenia lanceolata (Bloch, 1782) Railliet, 1892 Intermediate hosts: crustacean Auxiliary hosts: mollusc -Lymnaea auricularia Habitat: small intestine -posterior half Distribution: Cosmopolitan. Belarus (Kukar, 2012), Czech Republic and Slovakia (Barus et al, 1977;Hanzelova et al, 1995), Bulgaria (Marinova et al, 2013, Bangladesh (Anisuzzaman et al, 2005;Farjana et al, 2008;Aleya et al, 2019), USA and Mexico (Farias & Canaris, 1986), India -Assam region (Borah et al, 2018), Poland (Czaplinski, 1956). Azerbaijan -Guba, Khachmaz, Astara, Shabran, Zagatala, Masally, Ujar and Yevlakh (PL 47%, II 2-14 ind.)…”
Section: Genus: Drepanidotaenia Railliet 1892mentioning
confidence: 99%
See 3 more Smart Citations
“…Drepanidotaenia lanceolata (Bloch, 1782) Railliet, 1892 Intermediate hosts: crustacean Auxiliary hosts: mollusc -Lymnaea auricularia Habitat: small intestine -posterior half Distribution: Cosmopolitan. Belarus (Kukar, 2012), Czech Republic and Slovakia (Barus et al, 1977;Hanzelova et al, 1995), Bulgaria (Marinova et al, 2013, Bangladesh (Anisuzzaman et al, 2005;Farjana et al, 2008;Aleya et al, 2019), USA and Mexico (Farias & Canaris, 1986), India -Assam region (Borah et al, 2018), Poland (Czaplinski, 1956). Azerbaijan -Guba, Khachmaz, Astara, Shabran, Zagatala, Masally, Ujar and Yevlakh (PL 47%, II 2-14 ind.)…”
Section: Genus: Drepanidotaenia Railliet 1892mentioning
confidence: 99%
“…Intermediate hosts: Arthrapoda Habitat: faeces, small intestine Distribution: Cosmopolitan. Bangladesh -Sonarqaon province (Aleya et al, 2019). Sharma, 1943 Intermediate hosts: unknown Habitat: small intestine Distribution.…”
Section: Hymenolepis Diminuta Rudolphi 1819mentioning
confidence: 99%
See 2 more Smart Citations
“…Khanum et al (1997) reported trematode and nematode parasite are prevalent in domestic fowl where. Begum et al (2019) observed seven species of ectoparasite and thirteen species of endoparasite in domestic ducks. Among the two selected hosts, fowls were terrestrial birds while ducks were habituated to aquatic modes of life and consequently their feeding habits were also completely different.…”
Section: Introductionmentioning
confidence: 99%